2020
DOI: 10.22270/jddt.v10i4.4160
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical Study, Anatomical Study and Phytochemical Screening of Aristolochia longa L.

Abstract: Aristolochia longa L. (Aristolochiaceae) is used in Algerian traditional medicine. The ethnobotanical study conducted in the region of Setif (East Algeria) has as an objective of evaluating the potential of the region of Aristolochia longa L. used in the treatment of different diseases. A questionnaire was used which consisted of the diseases treated by this plant, the part of the plant used in the treatment and how to use this plant. The survey targeted 100 people from the local population. We also evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Many plants of the genus Aristolochia have often been reported as an important source of remedy in several studies. The typical species Aristolochia longa L. (Aristolochiaceae) is widely distributed in Algeria and known as 'Beroustoum' or 'El-Zarawend El Tawil' in Arabic, it is commonly used in traditional herbal medicine (Merouani et al 2017(Merouani et al , 2020 in the majority of cases for cancer treatment (Benaraba et al 2014). Despite the wide use of this plant by humans, little is known and few studies have reported the phytochemical and pharmacological properties of this plant.…”
Section: Introductionmentioning
confidence: 99%
“…Many plants of the genus Aristolochia have often been reported as an important source of remedy in several studies. The typical species Aristolochia longa L. (Aristolochiaceae) is widely distributed in Algeria and known as 'Beroustoum' or 'El-Zarawend El Tawil' in Arabic, it is commonly used in traditional herbal medicine (Merouani et al 2017(Merouani et al , 2020 in the majority of cases for cancer treatment (Benaraba et al 2014). Despite the wide use of this plant by humans, little is known and few studies have reported the phytochemical and pharmacological properties of this plant.…”
Section: Introductionmentioning
confidence: 99%